Indigenous Forage Species Evaluation and Variety Development in Ethiopia: A Historical Perspective - Ekule, Muluken; Wamatu, Jane; Mengistu, Solomon (International Livestock Research Institute, 2022)
A historical view of forage research in Ethiopia with a focus on native forage species.